Enhanced Fluoride Removal from Groundwater Using Napier Grass-Derived Adsorbent: Experimental and DFT Study - Somkiattiyot, Patcharaporn; Wongrueng, Aunnop; Induvesa, Phacharapol; Yodsin, Nuttapon; Phuphisith, Sarunnoud; Sittisom, Prattakorn; Rakruam, Pharkphum; Srisom, Wiratchon; Gavila, Patcharaporn; Chamnanprai, Supoj; Takizawa, Satoshi (Trends in Sciences, 2025)
Lab-scale experiments and Density Functional Theory (DFT) studies were carried out to investigate the efficiency of Napier grass-derived adsorbent (CNP_600) and alkaline modification (CNP_0.2NaOH_600) as low-cost adsorption materials for fluoride removal. CNP that had been treated with an alkaline solution cloud contained more fluoride than the CNP that had been used initially. The NaOH modification of prepared materials promoted a change in surface characteristics that could enhance fluoride removal efficiency. Those adsorbents fitted well with the pseudo-2nd-order kinetic model and declared that the adsorption process was chemisorption. The isotherm study exhibited the best fit with the Langmuir model, resulting in mono-layer adsorption. The experimental adsorption behavior of fluoride ions (F–) onto CNPs was investigated. The proposed adsorption process involved electrostatic attraction and hydrogen bonding, which were found to be consistent with the results of a Density Functional Theory (DFT) study. The results indicated that the -OH and -COOH groups on the CNPs displayed electron acceptors from the F– ions. Additionally, the fluoride removal of actual groundwater from the prepared adsorbents was 17 %. The small percentage of adsorption efficiency in groundwater was because of pH and co-exiting ions. Finally, the use of biomass waste as a biochar adsorbent to control the fluoride excess in groundwater in the problematic area could promote the sustainability of water safety for the community, especially in the northern part of Thailand. HIGHLIGHTS The adsorption process removes fluoride using Napier grass biochar (CNP_600) and NaOH functionalization (CNP_0.2NaOH_600). Based on the function groups of the materials, we can use the DFT study results to confirm the behavior of F–ions in the biomass samples. The experimental study’s adsorption mechanism followed a similar pattern to the DFT studies. This confirms that CNPs help F–ions form strong H-bonds. The O-H bond lengthened from 0.97 Å to 1.40 Å, confirming the strong interaction between CNP and fluoride ions. GRAPHICAL ABSTRACT